2021
DOI: 10.1002/lt.26365
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Risk Stratification for Nonalcoholic Fatty Liver Disease Among Living Liver Donor Candidates: A Proposed Algorithm

Abstract: To reduce waitlist mortality, living donor liver transplantation (LDLT) has increased over the past decade in the United States, but not at a rate sufficient to completely mitigate organ shortage. As a result, there are ongoing efforts to expand the living liver donor pool. Simultaneously, the prevalence of nonalcoholic fatty liver disease (NAFLD) in the general population has increased, which has significant implications on the pool of potential living liver donors. As such, a clinical assessment algorithm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…MRI-PDFF can be used to differentiate moderate or severe steatosis from mild or no steatosis with 93% sensitivity and 85% specificity and is commonly used at many transplant centers to quantify liver fat content. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI-PDFF can be used to differentiate moderate or severe steatosis from mild or no steatosis with 93% sensitivity and 85% specificity and is commonly used at many transplant centers to quantify liver fat content. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…MRI-PDFF can be used to differentiate moderate or severe steatosis from mild or no steatosis with 93% sensitivity and 85% specificity and is commonly used at many transplant centers to quantify liver fat content. 18,19 Previous studies have shown that there is little to no correlation between BMI and liver fat content. 20,21 Kramer et al 20 was a prospective study of 50 adults (mean BMI, 27.4; SD, 5.4) without known hepatic steatosis who underwent liver imaging with a variety of different imaging modalities, including proton density fat fraction, single-and dual-energy CT, gray-scale ultrasound, and ultrasound shear-wave elastography, with magnetic resonance spectroscopy as the reference.…”
Section: Discussionmentioning
confidence: 99%
“…The meta‐analysis concluded that CT had poor accuracy in detecting lower degrees of steatosis. In their proposed algorithm for detection of nonalcoholic fatty liver disease in living donors, Danis et al 37 . recommended MRI proton density fat fraction as the modality of choice for steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…had poor accuracy in detecting lower degrees of steatosis. In their proposed algorithm for detection of nonalcoholic fatty liver disease in living donors, Danis et al 37 recommended MRI proton density fat fraction as the modality of choice for steatosis. On the other hand, MRI appears to be a better tool, especially when combining MRI fat fraction and MRI elastogram in detecting and quantifying steatosis, especially when the threshold is >10%.…”
Section: Brown 2003 17mentioning
confidence: 99%
“…A systematic review and meta-analysis identified that >30% reduction of steatosis on MRI-PPF was associated with a significant histologic response (OR 6.98) and NASH resolution (OR 5.45). [ 31 ] Danis et al [ 32 ] proposed an algorithm to stratify patients using FIB-4<1.3 and NFS<−1.455 into low and moderate-high risk of steatosis, with MRI-PPF only for assessment of steatosis (<10% acceptable) in low risk and both MRI-PPF and MR Elastography (MRE) in moderate-high risk group. Steatosis greater than 10% and MRE>3kPa would prompt weight loss and re-evaluation, yielding a reported diagnostic accuracy of 83%, positive predictive value of 89%, and specificity of 90%.…”
Section: Hepatic Steatosismentioning
confidence: 99%